2017
DOI: 10.7324/rjc.2017.1041907
|View full text |Cite
|
Sign up to set email alerts
|

"CHARACTERISTICS AND MAGNETIC PROPERTIES OF CHITOSAN-COATED Fe3O4 NANOPARTICLES PREPARED BY EX-SITU CO-PRECIPITATION METHOD"

Abstract: Chitosan-coated iron oxide nanoparticles were synthesized by ex-situ co-precipitation method. Ammonia solution was dropped into the solution containing ferrous and ferric salts through a syringe pump to form Fe3O4 nanoparticles. Nanoparticles produced were then coated and crosslinked with chitosan and tripolyphosphate/sulfate, respectively. The physical and magnetic properties of chitosan-Fe3O4 nanoparticles were characterized using Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), and Electron Spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Chitosan-FA nanoparticle was formed by interaction between positive charge of the amino group in chitosan and cross-linker agent, sodium TPP, which has a negative charge. 14 The result showed that the chitosan-FA revealed a smaller size of particle compared to the nanoparticle prepared from chitosan as described in our previous research due to the addition of tween 80 during chitosan-FA NP preparation. The addition of folic group into chitosan polymer affected the molecular size of the polymer.…”
Section: Characterization Of Chitosan-fa Nanoparticlesupporting
confidence: 66%
“…Chitosan-FA nanoparticle was formed by interaction between positive charge of the amino group in chitosan and cross-linker agent, sodium TPP, which has a negative charge. 14 The result showed that the chitosan-FA revealed a smaller size of particle compared to the nanoparticle prepared from chitosan as described in our previous research due to the addition of tween 80 during chitosan-FA NP preparation. The addition of folic group into chitosan polymer affected the molecular size of the polymer.…”
Section: Characterization Of Chitosan-fa Nanoparticlesupporting
confidence: 66%
“…The Cu ion in the Zn-ferrite crystal increases the constant rate of 0.10 mmol min -1 and the Cu-ferrite see a reaction rate of 0.18 mmol min -1 . This activity of Cu containing ferrites can be demonstrated by the redox pair Cu + /Cu 2+ at the surface [24][25][26][27][28][29] .…”
Section: Ferrites As Catalytically By Hydrogen Peroxidementioning
confidence: 98%
“…In this study, chitosan was used as a stabilizing agent on the surface of the silver nanoparticles to prevent agglomeration. In our previous study, it was found that chitosan added as a coating agent on the surface of nanoparticles was able to prevent agglomeration in a sample of iron oxide nanoparticles by decreasing the size of iron oxide clusters [42].…”
Section: Synthesis Of Silver Nanoparticles With Kepok Banana Peel Ext...mentioning
confidence: 99%
“…agglomeration in a sample of iron oxide nanoparticles by decreasing the size of iron oxide clusters [42].…”
Section: Characterization Of Silver Nanoparticles Using Uv-vis Spectr...mentioning
confidence: 99%